Analisis Kerusakan Mesin Thresher pada PT Socfindo Seunagan Menggunakan Metode Failure Mode And Effects Analysis (FMEA) - Kasmawati, Kasmawati; Fajar, Ulul Al; Sofiyanurriyanti, Sofiyanurriyanti; Safitriyawi, Roja; Marlinda, Marlinda (Universitas Teuku Umar, 2025)
This study aims to analyze the damage of the Thresher machine at PT Socfindo Seunagan using the Failure Mode and Effects Analysis (FMEA) method as an effort to identify potential failures, causes, and impacts on the production process. The scope of the study focused on four main components of the thresher machine, namely the thresher drum, shaft and bearings, chain, and gearbox. The research method employed a combination of interviews, direct field observation, and literature reviews. Data analysis used the FMEA approach by determining the type of potential failure, causes, effects caused, control efforts, and calculating the Risk Priority Number (RPN) to determine repair priorities. The results showed that the damage that often occurred included bending/breaking in the thresher drum, cracks in the shaft and bearings, breaks in the chain, and cracks in the gearbox. The highest RPN value was found in the gearbox component at 224, followed by the chain with a value of 96, the thresher drum at 42, and the shaft and bearing at 36. This indicates that the gearbox is the most critical component that requires special attention in care and maintenance. The conclusion of this study is that thresher machine failure has the potential to significantly reduce CPO processing productivity if proper control is not implemented. Therefore, companies need to implement routine maintenance and periodic checks, with a primary focus on the gearbox components, to minimize the risk of damage, extend the machine's lifespan, and maintain optimal production flow.